Fatty Acid Composition and Antioxidant Activity of Tricholoma Imbricatum and T. Focale - Erhan Kaplaner; Mehmet Hüseyin Singeç; Mehmet Öztürk (Turkish Journal of Agriculture: Food Science and Technology)
Edible mushrooms are one of the important food source because of their tastes, and having high concentration of fatty acids and the other nutrients. In this study, fatty acid composition and antioxidant properties of Tricholoma imbricatum and T. focale were determined. The fatty acids were analysed by GC, and GC-MS while the antioxidant activity was tested using five complimentary methods; namely, β-carotene-linoleic acid, DPPH scavenging, ABTS scavenging, CUPRAC and metal chelating assays. Eight fatty acids were determined in hexane extract, and oleic acid was the major fatty acid with 46.4% and 35.0%, respectively. Palmitic acid (12.8%, and 5.12%) and lineloic acid (28.2% and 31.0%) were also detected in high amounts. In DPPH.scavenging and ABTS·+ scavenging assays, the methanol extract of T. imbricatum (IC50: 0.12±0.01 mg/mL for both assay) showed better antioxidant activity than those of T. focale (IC50>0.8±0.01, and IC50: 0.21±0.01 mg/mL). All extracts of T. focale exhibited good activity in β-carotene-linoleic acid assay while only the hexane extract of T. imbricatum showed activity. Both mushroom indicated moderate in cupric reducing power. Since the mushrooms are nontoxic and edible, both can be used in food industry as preservatives.